Effect of calcium on histamine release from pleural and peritoneal mast cells induced by catechol (Revista Española de Fisiología, 1986)
Histamine release from rat pleural and peritoneal mast cells induced by catechol (1, 10, 50, 250 microM and 1 mM) has been studied.The dose-response induced by catechol is non-cytotoxic, is not modified by purification of mast cells and is calcium independent.The sensitivity and maximum response to catechol is the same irrespective of the presence or absence of Ca++, except on purified pleural mast cells, that showed a plateau response at 250 microM catechol in the absence of Ca++, and on unpurified peritoneal mast cells which exhibited a lower maximum response equally in the absence of Ca++.The release is induced by catechol at concentrations as low as 50 microM in all cases, and the maximum response is reached at 1 mM.